A Study on Impact of Workforce Diversity on Employee Performance with Reference to IT Companies - Shekhawat, Shakti Singh; Sarangdevot, SS (International Journal of Computer Sciences and Engineering, 2025)
Workforce Diversity is one of the most prominent indicators of changing global trends and markets. In order to determine whether a varied workforce has an effect on employee performance, this research was conducted to examine the workforce diversity and its effect on employee performance in IT organisations. India's IT sector is expanding quickly. Workforce diversity is a growing problem in the corporate world today since it presents organisations with a challenge as well as a chance that, if not effectively handled, can have an impact on employee's performance and, ultimately, the organisation. This study focuses on Age diversity, Educational Background diversity, Religious diversity, Work Experience diversity& Attitude diversity, all of which are measured in relation to employee performance. The study's research offers significant insight into the diversity management strategies being used by IT industry organizations. The survey unequivocally highlights the need for organizations to take action to manage diversity in order to maximize employee potential and gain a competitive edge